Flood hazard simulation for development plans in urban environment: a case study in Naga City, the Philippines - Abd. Rahman, Muhammad Zulkarnain; Ibrahim, Ab. Latif; Wan Kadir, Wan Hazli; Alkema, Dinand (2007)
Accurate and detailed terrain model are essential for hydrodynamics modelling especially in urban area. However, one of the main problems is frequent changes of land use in major cities, where frequent updating of the digital terrain model (DTM) for flood modelling might be needed. This paper presents one of the feasible approaches to assess the impact of developments on flood behaviours in an urban area. The input terrain model for hydrodynamic modelling is constructed through integrating different elevation datasets derived from various sources. Finally, the impact of the development on flood behaviour is made through detailed investigation on changes in flood hazard area. In the Digital Terrain Model development, the semivariogram of the geostatistical approach is used to investigate the effect of integrating various sources of elevation datasets. Furthermore, four interpolation methods were used for terrain interpolation, namely Australian National University's Digital Elevation Model algorithm (ANUDEM), Kriging, Polynomial and Triangulated Irregular Network (TIN). The assessments of the terrain models are based on the â€œPercentile Vertical Accuracy Assessmentâ€, the distribution of errors and visual assessment of the DTMs. In this study, it was found that the DTM produced by Kriging is better than the DTMs produced by other interpolators and it fits with the requirements for the flood modelling purpose. In conjunction, two sets of Digital Surface Model (DSM) were constructed to represent the situation of Naga City, before and after the developments. The flood modelling is based on the 1D and 2D SOBEK flood model that used to simulate the flood events of 2, 5, 10 and 17.5 years return period flood. According to the results, it was proved that by simply elevating ground terrain in particular areas might not be a good solution for flood mitigation. This approach could create another flood problem in vicinity area.